Developing the Indian Debt Capital Markets: Small investor Perspectives - Planning Commission (Planning Commission, 2003)
The secondary debt market in India is practically non-existent. This paper argues that with the recent economic reforms, an efficient and active debt market, particularly in long-term private debt instruments, is essential for the country to realize the full benefits of the reform process and to achieve its potential. It is further argued that the presence of small investors is critical to this process, given the limitations of the institutional investors. The essential conditions for a well-functioning debt market are identified from a study of the U.S. and European markets, and an assessment made of their presence in India. Specific concerns of small investors in the Indian context are described, and suggestions made as to how these can be addressed.
Perspective Planning Division Planning Commission Government of India